The Efficacy of Combination Therapy Using Atropine and Orthokeratology in Limiting Myopia Progression in Comparison to Atropine and Orthokeratology Monotherapy—A Systematic Review - Qasim, Muhammad; Sana Balouch, Malab; Shahbaz, Muhammad; Martins Jorge, Jorge Manuel; Botelho Fernandes, Paulo (Canadian Journal of Optometry, 2025)
Myopia a growing global public health issue, particularly amongst children and adolescents raised the issues of addressing not only the diseases up-going trend but also its management effectiveness. This review article is meant to evaluate the efficacy of combination therapy using atropine and orthokeratology in limiting myopia progression in comparison to atropine and orthokeratology monotherapy. In this study, we accessed PubMed, Web of Science and other databases to search for the articles address the effectiveness of combined therapy in myopia management rather than its monotherapy. Data was collected systematically from 8 studies on combination therapy, 6 on Orthokeratology alone, and 6 on Atropine monotherapy focusing changes in axial length of the individuals underwent the prescribed therapies. Statistical analysis was done using Python, Pandas Scikit Learn, SciPy & MatPlotLib for data visualization, accuracy and efficiency to get valid test results. This review article study revealed that combination therapy resulted in a mean reduction in axial length of 0.10 mm to 0.28 mm, significantly outperforming Atropine monotherapy (0.02 mm to 0.87 mm) and Orthokeratology alone (0.19 mm to 0.36 mm). The combination therapy demonstrated large effect sizes (Cohen’s d of 1.59 and 1.95) compared to individual treatments indicating a synergistic effect. However, variability in study designs and the limited availability of long-term data reinforces the need for further research. This review highlights the potential of combination therapy as a superior approach to myopia management, advocating for its consideration in clinical practice to mitigate the growing burden of myopia Keywords: Myopia Management, Atropine, Orthokeratology, Combination Therapy, Review